Analisis Efektivitas Biaya dan Manfaat Pelatihan Perthitungan pada UMKM - Valentina Monoarfa; Aminarti Daud; Nanda Utuli; Sri Rahmalia Saleh; Noviyanti Fatimah Riyadi (Economic Reviews Journal, 2025)
The training in calculation for Micro, Small, and Medium Enterprises (MSMEs) plays a crucial role in enhancing the managerial and financial skills of business actors. This study employs a descriptive qualitative approach to evaluate the cost-effectiveness and benefits of the training. The results indicate that training participants experience significant improvements in transaction recording, financial report management, and business decision-making. With a better understanding of financial management, MSMEs can enhance their competitiveness and sustainability. Therefore, investment in this training has proven to yield positive results and is worth continuing.